Functional swallowing outcomes related to radiation exposure to dysphagia and aspiration‐related structures in patients with head and neck cancer undergoing definitive and postoperative intensity‐modulated radiotherapy. Issue 2 (22nd November 2021) - Charters, Emma; Bogaardt, Hans; Clark, Jonathan; Milross, Chris; Freeman‐Sanderson, Amy; Ballard, Kirrie; Britton, Rafe; McCabe, Natalie; Davis, Hannah; Sullivan, Tom; Wu, Raymond
Abstract: Background: The relationship between swallowing outcomes and radiotherapy dose to dysphagia and aspiration‐related structures (DARS) may be different following definitive versus postoperative radiotherapy (PORT) for mucosal head and neck cancer (HNC) and has not been well‐studied. Method: Patient‐ and clinician‐reported swallowing measures were prospectively collected at six time points from baseline to 24 months postradiotherapy HNC. Radiotherapy plans were retrospectively analyzed to assess dose delivered to DARS. The association between swallowing outcomes and participant demographics, tumor characteristics, and radiotherapy dose in definitive and postoperative treatment cohorts was assessed. Results: Ninety‐three participants who received radiotherapy for HNC were included in the analysis ( n = 49 definitive radiotherapy for laryngeal/pharyngeal primary tumors and n = 44 postoperative PORT for predominantly oral cavity/salivary gland tumors). Participants undergoing PORT had lower doses to DARS than those undergoing definitive RT. High dose to the pharyngeal constrictors and base of tongue for definitive RT and the esophageal inlet, supraglottic larynx and cervical esophagus for the PORT group were associated with worse swallowing function. Conclusion: Radiation dose to DARS is associated with post‐treatment swallowing outcomes. These dose/outcome relationships may vary between the definitive and postoperative settings.